The effects of empowered nursing management on the job performance of the head nurse as perceived by staff nurses - Molon, Edna Del Rosario
Back in the '70s, empowerment of nurses was unthikable as medicine has historically lorded it over the health field. The '80s brought the concepts of accountability, participation, partnership and decentralization to the fore. Nurses in the Western world rallied to practice without numerous and professionally extraneous restraints, calling consequently for a restructuring of the work environment to allow for growth and self-determination. High level participation of allied health professionals, team work, trust, risk-taking and willingness to practice equity in both role and relationship became the battle cry. To facilitate the transformation, the nurse leader must engage in empowered nursing management, the practice of working with and through others through decision-making aimed at controlling one's practice. It entails, among other thins, being able to make decisions without having to go to the top, a creative yet risk taking behavior essential to empowerment.This study sought to determine the extent to which head nurses in selected private tertiary hospitals practice empowered nursing management (if at all present). It, likewise, posited the following hypotheses:H1: There is a significant relationship between selected socio-demographic characteristics of the head nurse (age, sex, civil status, education and years of experience as a head nurse) and empowered nursing management.H2: There is a significant relationship between empowered nursing management and the head nurse's job performance.As empowered nursing management manifests itself in self-governance through patient, personnel and unit management, practice partnership with other health professionals and participative management, the practice of empowerment in nursing management was measured along these criteria.This study was conducted in seven (7) private tertiary hospitals with 250 and more bed capacity in the city of Manila and Quezon City. The study sample was composed of 83 randomly selected day-duty head nurses whose practice of empowered nursing management were rated by two randomly selected permanent staff nurses (N = 166) who have been wit her for at least a year or so to prevent self-reports that did not reflect actual behavior. The head nurses' job performance was rated by 39 supervisors under whose jurisdiction they fell.A two-part questionnaire was designed by the investigator after literature review and interviews with nurse managers of UP-PGH Medical Center to extract additional concepts on head nurse decision-making in her area. The first part of the research tool asked for personal data of the respondents. The second part was a 30-item situational tool that tested the head nurse's decision-making skill. To be considered an empowered manager, the head nurse must get - 4 of the empowered choices in all components of empowered nursing management. Thus, a total correct score of - 20 can only mean an empowered practice if all components (self-governance has three sub-components) were satisfied. Much importance was placed on self-governance because the decisions to be made there were in the immediate area of responsibility of the head nurse.